2018
DOI: 10.1039/c8ra03687j
|View full text |Cite
|
Sign up to set email alerts
|

The self-assembly of monosubstituted BODIPY and HFBI-RGD

Abstract: A novel fluorescent probe was constructed by the self-assembly of monosubstituted BODIPY and a novel targeted hydrophobin named hereafter as HFBI-RGD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In recent years, remarkable efforts have been devoted to the development of functionalities of BODIPY derivatives. [65][66][67][68][144][145][146][147][148] The molecular BODIPY and aza-BODIPY dyes have been investigated in a diverse range of applications, such as fluorescent probes, [149][150][151][152] ion recognition, 153,154 biological imaging, [155][156][157][158] photothermal and photodynamic therapy, [159][160][161][162][163][164] organic solar cells, 146 and liquid crystalline materials. 165 In this part we focus on those applications of (aza-)BODIPY dyes specifically connected with their self-assembly pathways.…”
Section: Pathway-dependent Functionalities Of (Aza-)bodipy-based Dye ...mentioning
confidence: 99%
“…In recent years, remarkable efforts have been devoted to the development of functionalities of BODIPY derivatives. [65][66][67][68][144][145][146][147][148] The molecular BODIPY and aza-BODIPY dyes have been investigated in a diverse range of applications, such as fluorescent probes, [149][150][151][152] ion recognition, 153,154 biological imaging, [155][156][157][158] photothermal and photodynamic therapy, [159][160][161][162][163][164] organic solar cells, 146 and liquid crystalline materials. 165 In this part we focus on those applications of (aza-)BODIPY dyes specifically connected with their self-assembly pathways.…”
Section: Pathway-dependent Functionalities Of (Aza-)bodipy-based Dye ...mentioning
confidence: 99%
“…They demonstrated that encapsulating quantum dots allowed for efficient phase transfer while maintaining a significant portion of emission characteristics, and allowing for additional conjugation for biological imaging applications [70]. HFBI fused to an RGD motif was recently employed as a solubilizing agent for a hydrophobic boron-dipyrromethene (BODIPY) dye, with the RGD motif on the encapsulated dye causing effective labeling of tumors in nude mice [71].…”
Section: Applicationsmentioning
confidence: 99%
“…Recently, boron dipyrromethene (BODIPY) derivatives are a concerned near-infrared fluorescent dye with the characteristic of high extinction coefficient, high fluorescence quantum yield, narrow absorption and emission bands, excellent photostability [ [10] , [11] , [12] , [13] , [14] , [15] ]. Therefore, the BODIPY derivatives have attracted immense research interests as these assemblies offer various applications in the areas like pharmaceuticals, stabilizations of organic dyes/drugs, targeted drug delivery [ [16] , [17] , [18] ], and, of course, as photosensitizers have also been applied in drug tracking, cancer diagnosis and fluorescent switch [ [19] , [20] , [21] ]. However, the absorption and emission wavelength of BODIPY dye are difficult to reach the near-infrared region which had more absorption disturbance in bio-imaging.…”
Section: Introductionmentioning
confidence: 99%